Influences and aspirations in the production of national projects in Lebanon and Kuwait - Mazzetto, Silvia (2020)
Purpose By looking at a selection of iconic modern projects designed by or commissioned to the prominent but not well-examined architect Sami Abdul Baki both in Lebanon and Kuwait during his most productive years in the 50s, this paper attempts to identify first main trends, influences and ideologies that shaped these works at the peak of modern architectural development in the region. Through these examples, the paper then aims at retracing predominant trajectories of intellectual capital exchange and transfer of knowledge between Lebanon and Kuwait. These can go far beyond their territorial boundaries, without claiming a single grand-narrative that describes the modern architectural development in any of the two countries. Design/methodology/approach The data collected from discourse analysis, interviews and biographical notes were mapped into a schematic diagram illustrating a complex network of connections and multidisciplinary involvement in projects. Findings However, the outcome did not generate a dominant theme for the projects or expertise of the architect. Originality/value It is very likely that Sami Abdul Baki's strong political dimension and quality as a mediator or facilitator in addition to his strong network of contacts played a significant role in the project commissions that he has won as an architect/engineer in Kuwait, Lebanon, Germany and other countries.